(untitled) (Journal of Madenat Alelem, 2012)
The concept of wideband coded modulation has been in existence for many years. It was predominately utilized in many applications due to its inherent resistance to noise, including jamming and low probability of intercept. For this reason, it was the communication method of choice in various situations. The TTCM has been shown to be more efficient than TCM for transmissions over AWGN channels and narrowband fading channels. The multi-path channel model is characterized by its discretized symbol-spaced COST207 Typical Urban (TU) channel impulse response. The Rayleigh multipath channel is also discretized. Therefore, OTHMA can be applied as a multiple access scheme for low power, large scale, and low activity networks in UWB impulse radio communications. The performance of TTCM Burst-by-Burst Adaptive Wideband Coded Modulation system is tested in a Semi-realistic channel model that is based on an extensive set of outdoor channel measurements. Through semi-analytical evaluations of the bit error probability, we show that the TTCM Burst-by-Burst Adaptive Wideband Coded Modulation system is almost has good BER performance. Also, a comparison between the BER performances of many channels has been done.